THE NECESSITY OF FORMING SPEECH ACTIVITY IN PRESCHOOL EDUCATIONAL INSTITUTION STUDENTS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article investigates the role and effectiveness of the extratextual teaching method in fostering speech activity among preschool-aged children. It analyzes the impact of visual, audiovisual, and movement-based educational resources on speech development through cognitive approaches. The study demonstrates the high efficacy of this method using scientifically grounded methodological solutions and experimental results.